PARADOKS PEMAKZULAN PRESIDEN/WAKIL PRESIDEN DALAM PRINSIP NEGARA HUKUM - M. Saoki Oktava; Riska Ari Amalia (Media Keadilan: Jurnal Ilmu Hukum, 2019)
The promulgation of the implementation of the Constitutional Court's decision is in the spotlight of other State Institutions that have repealed articles that have been canceled by the Constitutional Court in the new Law. Likewise with the authority of the Constitutional Court. In the process of presidential impeachment by the MPR there are indications that the Constitutional Court's Decision stating that the president and / or vice-president were proven guilty by the Constitutional Court can also be set aside, given the political process in the MPR which refers to the minimum decision-making conditions. The president is attended by at least ¾ of the total number of MPR members and is approved by at least 2/3 of the total members present. The research method used is a normative research method with the statue approach approach. Sources and Types of Legal Materials namely primary legal materials, secondary legal materials and tertiary legal materials related to this study. From the results of the study, the paradox of the presidential impeachment in the principle of the rule of law, the process of presidential impeachment according to the 1945 Constitution of the Republic of Indonesia NRI is carried out by political and legal mechanisms. The Basic Strength of the Constitutional Court Decision in the Context of Presidential Decree In State Principles is Article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia NRI "the state of Indonesia is a constitutional State" adjudicates at the first and last level that causes the Constitutional Court's decision to be final and binding for the MPR in impeaching the President and or Deputy PresidentKeywords: paradox, presidential election, principles rule of lawABSTRAKPromlematika implementasi putusan MK menjadi sorotan terhadap Lembaga Negara lain yangmemuculkan kembali pasal-pasal yang telah dibatalkan oleh MK dalam Undang-undang yang baru. Demikian juga terhadap wewenang MK Dalam proses pemakzulan presiden oleh MPR ada indikasi Putusan MK yang menyatakan presiden dan atau wakil presiden terbukti bersalah oleh MK dapat juga dikesampingkan, mengingat proses politik di MPR yang mengacu pada  syarat pengambilan keputusan minimal syarat dukungan Pemakzulan Presiden dan/atau Wakil Presiden minimal dihadiri oleh sekurang-kurangnya ¾ dari jumlah anggota MPR dan disetujui oleh sekurang-kurangnya 2/3 dari jumlah anggota yang hadir. Metode Penelitian yang digunakan adalah metode penelitian normatif dengan metode pendekatan perundanng-undangan (statue Approach). Sumber dan Jenis Bahan Hukum yaitu Bahan hukum primer, Bahan Hukum Skunder dan Bahan Hukum Tersier yang berkaitan dengan penelitian ini. Dari hasil penelitian, terhadap paradoks  pemakzulan presiden dalam prinsip Negara hukum, proses pemakzulan presiden menurut UUD NRI Tahun 1945 dilakukan dengan mekanisme polik dan hukum. Dasar Kekuatan Putusan MK dalam Konteks  Pemakzulan Presiden Dalam Prinsip Negara adalah Pasal 1 ayat 3 UUD NRI Tahun 1945 “negara Indonesia adalah Negara hukum” mengadili pada tingkat pertama dan terakhir yang menimbulkan  putusan MK bersifat final dan mengikat bagi MPR dalam melakukan Pemakzulan Presiden dan atau Wakil Pesiden.Kata kunci: paradoks pemakzulan presiden, pinsip negara hukum